Village Development and Sustainable Employment: Valuable Lessons from West Seram District - Leroy Samy Uguy; Esther Kembauw; Liza Handoko; Marlita. H. Makaruku; Anna. Y. Wattimena (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This research aims to analyze the impact of village development on sustainable employment in West Seram District, focusing on strategies implemented to improve the local economy and reduce community dependence on seasonal sectors. A qualitative approach with a case study method was used in this research, involving in-depth interviews with key stakeholders, such as village heads, local business actors, and village communities. In addition, secondary data from government reports and academic literature were used to enrich the analysis. The results show that village development integrated with entrepreneurial skills development and local resource management can create more stable and sustainable employment. However, this study also found several constraints, particularly limited infrastructure and access to technology. These limitations pose a major challenge in achieving sustainable employment in rural areas. The implications of these findings suggest the importance of policies that support community capacity building and sustainable infrastructure investment to facilitate economic growth in villages. This research provides insights for policymakers and village development practitioners in designing more effective strategies for sustainable employment in rural areas.